Mathematics in Vytautas Magnus University in 1940–1943 - Pekarskas, Vidmantas Povilas (Lietuvos matematikos rinkinys, 2011)
On overview of pedagogical and methodical activities of Vytautas Magnus University mathematicians in 1940–1943 is given in this paper. Bibliographic data of Vytautas Magnus University mathematicians are supplemented by new facts. An analysis of the first and the third parts of J. Valukonis book “Lectures in High Mathematics” published in 1943 is presented in the paper. The second part of this book has not been found yet in Lithuania.
Keywords: Vytautas Magnus University mathematicians; mathematics programs; mathematics textbook